Benefits of new Driver Training Curriculum (KPP) implementation as a means for road user awareness / Siti Faizzatul Aini Misyan - Misyan, Siti Faizzatul Aini; Badrillah, Muhammad Izwan; Zulfakar, Mohd Hafiz; Tengku Aziz, Tengku Nurul Aishah (UiTM Cawangan Johor, 2018)
This study is conducted to investigate the benefits of new Driver Training Curriculum (KPP) implementation as a means for road user awareness. In Malaysia, the issue of traffic accidents has become a serious social problem. Apart from that, governments and private sectors spend huge resources on road safety programmes, with the target of achieving zero fatality and reducing injury. Due to this case, the Government has launched a new KPP in 2014 and implemented in 2015. This programme aimed to improve the driver's knowledge and stricter license approval. The previous KPP equipped drivers with only cognitive and psychomotor skills with less emphasis on affective skills while the current KPP was developed to produce more courteous and disciplined drivers. This study is conducted in Muar area. In this study also, the researchers used questionnaire as the method of collecting data and information. A total of 150 were sampled for the study drawn from old and new KPP group. Since this programme has just been implemented by Road Transport Department (RTD), this study opens up many new research opportunities in the future.